Influence of nanoparticles inclusion on the production of bioethanol from corn stalks and leaves - Saetang, Nuttapong; Tipnee, Sawitree (Maejo International Journal of Energy and Environmental Communication, 2022)
Bioethanol is a viable alternative to petroleum-derived fossil fuels. It is renewable, low-cost, and the preferred fuel for most developing countries worldwide. Although it is possible to make bioethanol from corn stalks and leaves wastes, second-generation biofuels made from agricultural waste feedstocks represent a significant step forward. In the present research, nickel oxide (NiO) nanoparticles (NPs) were used as a biocatalyst to achieve maximum ethanol output. The pretreatment of 2% NaOH with NiO NPs, 15-min autoclave condition, showed the highest total and reducing sugar yield was 162.69 g/L and 43.75 g/L. After hydrolysis, the suitable total and reducing sugar yield of 185.43 g/L and 125.42 g/L was chosen for further fermentation with the expansion of Saccharomyces cerevisiae cells. Separate hydrolysis and fermentation (SHF) using corn stalk and leaf waste was significantly assisted by incorporating a nanocatalyst; ethanol concentration was increased to 15.8 g/L at 24 hours incubation period. The study revealed critical information regarding ways NiO NPs could be employed to improve the efficiency of the ethanol production bioprocess.